Cribado de parto prematuro con progesterona salival - Haye M., M. Teresa; Garrido P., Maritza; Aleuanlli A., M. Cristina; Parra-Cordero, Mauro (Revista Hospital Clínico Universidad de Chile, 2016)
Preterm birth is the most frequent cause of perinatal morbidity and mortality, especially before 34 weeks. Current screening methods include medical history of preterm delivery and ultrasound assessment of cervix length during the second trimester of pregnancy, which give a detection rate of approximately 65% with a false positive rate of 10%. Vaginal progesterone therapy has proved to reduce the risk of early preterm delivery by 50% in patient under risk. This might suggest that preterm pregnancies have lower levels of progesterone compared to term pregnancies. Although, the prediction of prematurity using biomarkers, including plasma progesterone, has been researched for several years, none of them have proved to be associated with preterm delivery. However, measuring salivary progesterone has already been suggested to be a potential biomarker associated with prematurity in pregnancies at high risk of preterm delivery. Saliva is a fluid that reflects only the free fraction of the biologically active steroidal hormone, and thus is more representative measure than the total plasma progesterone, which is the one usually measured in laboratories. For these reasons, the aim of our study is to evaluate whether the assessment of salivary progesterone can be used as a screening test for prediction of preterm delivery less than 34 weeks in pregnant women who attended at our Fetal Medicine Unit at 11-14 and 20-25 weeks of gestation.